Non-alpha-adrenergic effects on systemic vascular conductance during lower-body negative pressure, static exercise and muscle metaboreflex activation - Kiviniemi, A. M.; Frances, M. F.; Rachinsky, M.; Craen, R.; Petrella, R. J.; Huikuri, H. V.; Tulppo, M. P.; Shoemaker, J. K. (Acta Physiologica, 2012)
Aim This study tested the hypothesis that non‐α‐adrenergic mechanisms contribute to systemic vascular conductance (SVC) in a reflex‐specific manner during the sympathoexcitatory manoeuvres. Methods Twelve healthy subjects underwent lower‐body negative pressure (LBNP, −40 mmHg) as well as static handgrip exercise (HG, 20% of maximal force) followed by post‐exercise forearm circulatory occlusion (PECO, 5 min each) with and without α‐adrenergic blockade induced by phentolamine (PHE). Aortic blood flow, finger blood pressure and superficial femoral artery blood flow were measured to calculate cardiac output, SVC and leg vascular conductance (LVC) during the last minute of each intervention. Results Mean arterial pressure (MAP) decreased more during LBNP with PHE compared with saline (−7 ± 7 vs. −2 ± 5%, P = 0.016). PHE did not alter the MAP response to HG (+20 ± 12 and +24 ± 16%, respectively, for PHE and saline) but decreased the change in MAP during PECO (+12 ± 7 vs. +21 ± 14%, P = 0.005). The decrease in SVC and LVC with LBNP did not differ between saline and PHE trials (−13 ± 10 vs. −17 ± 10%, respectively, for SVC, P = 0.379). In contrast, the SVC response to HG increased from −9 ± 12 with saline to + 5 ± 15% with PHE (P = 0.002) and from −16 ± 15 with saline to +1 ± 16% with PHE during PECO (P = 0.003). LVC responses to HG or PECO were not different from saline with PHE. Conclusions Non‐α‐adrenergic vasoconstriction was present during LBNP. The systemic vasoconstriction during static exercise and isolated muscle metaboreflex activation, in the absence of leg vasoconstriction, was explained by an α‐adrenergic mechanism. Therefore, non‐α‐adrenergic vasoconstriction is more emphasized during baroreflex, but not metaboreflex‐mediated sympathetic activation.